2015
DOI: 10.1097/dbp.0000000000000190
|View full text |Cite
|
Sign up to set email alerts
|

A Question of Love and Trust? The Role of Relationship Factors in Adolescent Sexual Decision Making

Abstract: Objective While representing only 25% of the sexually active population, 50% of all new STI infections occur among young people, mostly due to inconsistent condom use. Critically, the majority of adolescent sexual activity takes place in the context of romantic relationships, thus it is important to understand how relationship factors may influence decision-making about the use, or not, of protection. Method We utilized a mixed method approach to investigate the extent to which relationship length, degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
16
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 31 publications
3
16
0
3
Order By: Relevance
“…Ultimately, these findings are particularly intriguing in light of behavioral studies showing different patterns of sexual decision-making by gender (62). The sample presented with gender differences in pubertal development.…”
Section: Discussionmentioning
confidence: 99%
“…Ultimately, these findings are particularly intriguing in light of behavioral studies showing different patterns of sexual decision-making by gender (62). The sample presented with gender differences in pubertal development.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, based on emerging empirical work in this area [55], gender differences may exist within mesocorticolimbic reward and emotion regulation pathways (VTA, insula/ACC, striatum/NAcc, limbic systems), although the scope, size, and direction of these relationships has yet to be established. These developmental gender differences would be in line with the broader behavioral sexual decision-making literature, which suggests that adolescent girls are more likely than boys to have sex to bolster or advance emotional aspects of relationship development (to foster intimacy, love, and trust) [3]. While empirical studies in this area are needed, we posit that there may be neurocognitive and behavioral differences in adolescent male sexual decision-making across the dimension of reward, particularly in the early years of sexual activity.…”
Section: Toward a Model Of The Neurocircuitry Of Adolescent Sexual Riskmentioning
confidence: 58%
“…The impact of this shift is that neural organization underlying sexual decision-making may manifest differently for adolescent females versus males. For example, the human behavioral literature indicates that adolescent females seek sexual interactions to foster relationship factors (getting and/or keeping a partner), rather than for physical reward (as is the case for adolescent males) [3]. Studies with adult humans have also shown gender differences in willingness to engage in sexual encounters, differences in sexual arousal and the sexual double standard [54].…”
Section: Developmental Neurocognitive Differences By Gendermentioning
confidence: 99%
See 2 more Smart Citations